2019
DOI: 10.1186/s12885-019-6413-7
|View full text |Cite|
|
Sign up to set email alerts
|

Human papillomavirus type 18 oncoproteins exert their oncogenicity in esophageal and tongue squamous cell carcinoma cell lines distinctly

Abstract: BackgroundIncreasing evidence indicates an etiological role of human papillomavirus (HPV) in head and neck cancers, particularly oropharyngeal squamous cell carcinoma (OPSCC). However, the association between HPV and other cancers, including esophageal and tongue remains unclear. This study delineated the molecular characteristics of HPV18 E6 and E7 in esophageal (EC109 and EC9706) and tongue (Tca83) cancer cell lines with reference to cervical cancer (HeLa).MethodsWe analysed the HPV transcription profiles of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…8 Previous gene expression studies from bulk transcriptional data have largely revealed transcriptional variation that may affect prognosis. 9 However, one of the major limitations is that bulk sequencing of tumor samples is unable to identify small subsets of tumor tissues. As a revolutionary method, single-cell RNA sequencing (scRNA-seq) has been widely used in various fields to dissect cellular compositions and characterize molecular properties of complex tissues.…”
Section: Introductionmentioning
confidence: 99%
“…8 Previous gene expression studies from bulk transcriptional data have largely revealed transcriptional variation that may affect prognosis. 9 However, one of the major limitations is that bulk sequencing of tumor samples is unable to identify small subsets of tumor tissues. As a revolutionary method, single-cell RNA sequencing (scRNA-seq) has been widely used in various fields to dissect cellular compositions and characterize molecular properties of complex tissues.…”
Section: Introductionmentioning
confidence: 99%
“…This assay is carried out as described previously ( 29 ). Approximately 2 × 10 5 U-2 OS cells were plated onto coverslips.…”
Section: Methodsmentioning
confidence: 99%
“…Epidemiological surveys have proven that nitrosamines and their precursors may increase the risk of EC. This research suggests that the aforementioned risk factors are probably involved in the development or the progression of EC. In addition, HPV could play an etiological role in EC in the presence of other essential cofactors such as environmental and genetic predisposition . Previously, we found that nitrosamines exposure is involved in the carcinogenesis of esophageal epithelia in the high incidence area of Huai’an …”
Section: Introductionmentioning
confidence: 97%
“…In addition, HPV could play an etiological role in EC in the presence of other essential cofactors such as environmental and genetic predisposition. 17 Previously, we found that nitrosamines exposure is involved in the carcinogenesis of esophageal epithelia in the high incidence area of Huai'an. 18 N-Methyl-N′-nitro-N-nitrosoguanidine (MNNG) is an environmental pollutant with high carcinogenicity and mutagenicity and is a synthetic N-nitroso compound used to replace nitrosamine compounds in nature to study its role in tumor formation.…”
Section: Introductionmentioning
confidence: 99%